Can nitrogen supersede host identity in shaping the community composition of foliar endophytic fungi in an alpine meadow ecosystem? - Meng, Yiming; Zhang, Qi; Shi, Guoxi; Liu, Yongjun; Du, Guozhen; Feng, Huyuan (Frontiers in Microbiology, 2022)
The availability of limiting nutrients plays a crucial role in shaping communities of endophytes. Moreover, whether fungal endophytes are host specific remains controversial. We hypothesized that in a harsh and nitrogen (N)-deficient area, diversity and community composition of foliar endophytic fungi (FEF) varied substantially among plots with experimentally elevated levels of macronutrients, and thus N availability, instead of host-species identity, would have greater influence in structuring fungal communities at different scales. We also expected an important subset of taxa shared among numerous host species and N gradients forming a community‐wide core microbiome. We measured leaf functional traits and community structure of FEF of three commonly seen species in an alpine meadow nested with a long-term N fertilization experiment. We found that host plant identity was a powerful factor driving the endophytic fungal community in leaves, even in habitats where productivity was strongly limited by nitrogen (p < 0.001). We also found that within the same host, nitrogen was an important driving force for the composition of endophytic fungi community (p < 0.05). In addition, leaf carbon content was the most important functional trait that limited the diversity of endophytic fungi (p < 0.001). Finally, we documented a distinct core microbiome shared among our three focal species and the N gradients.